Reducing the burden of active surveillance monitoring examinations in prostate cancer: Insights from real-world data to inform clinical practice - Cristina Marenghi; Fabio Badenchini; Barbara Avuzzi; Mario Achille Catanzaro; Alessandra Casale; Alessia Casbarra; Laura Cattaneo; Melanie Claps; Valentina Guadalupi; Alberto Macchi; Antonella Messina; Sebastiano Nazzani; et al. (Tumori Journal, 2026)
Background: Active surveillance (AS) is standard for early-stage prostate cancer, though intensive monitoring continues due to concerns about reclassification to Grade Group (GG) ⩾ 2. We hypothesized that simple and inexpensive clinical parameters could identify patients with indolent disease for whom less intensive monitoring is safe. Methods: We analyzed upgrading to ISUP Grade Group (GG) ⩾ 2 in a large cohort of low-risk prostate cancer (PCa) patients on AS. We used mixed-effects logistic regression to develop a model predicting non-upgrading at the next follow-up biopsy, based on routine time-updated clinical-pathological variables. Results: While annual reclassification persisted at a rate between 10.4% and 17.5% up to the 7th year, upgrades were predominantly GG2. Routine parameters powerfully stratified risk. Patients with a very unfavorable Prostate Specific Antigen (PSA) doubling time had a 40.5% upgrading rate versus 9.5% for those with a favorable value. The final model is based on baseline PSA density and number of positive cores, time-updated age and PSA doubling time category, detection of cancer in the last surveillance biopsy. The model showed moderate discrimination (0.73) in predicting non-upgrading. Conclusions: Many patients on AS have indolent disease but steady upgrading justifies monitoring. A model using simple, routine parameters and PSA doubling time can identify those at minimal risk of reclassification, enabling a safe reduction in biopsy intensity. This advocates for a risk-adaptive AS protocol, reserving advanced tools like MRI or biomarkers for the few higher-risk cases.